2018
DOI: 10.3892/ijo.2018.4667
|View full text |Cite
|
Sign up to set email alerts
|

DKK3 knockdown confers negative effects on the malignant potency of head and neck squamous cell carcinoma cells via the PI3K/Akt and MAPK signaling pathways

Abstract: Dickkopf-related protein 3 (DKK3), which is a member of the Dickkopf WNT signaling pathway inhibitor family, is considered to be a tumor suppressor, due to its reduced expression in cancer cells and its ability to induce apoptosis when overexpressed by adenovirus. However, our previous study demonstrated alternative functions for DKK3 in head and neck squamous cell carcinoma (HNSCC). Our study reported that DKK3 expression was predominantly upregulated in HNSCC cell lines and tissue samples, and its expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Inhibition of these pathways can be an excellent target for cancer therapy. In addition, MAPK and Wnt pathways activated are a marker of poor prognosis in human oral cancer, and persistent MAPK activation in it is associated with enhanced cellular and tumor growth 31 , 32 . The high cytotoxic effect of anethole in oral cancer cells at low concentration but in normal gingival cells, it has a marginal effect at low concentration, but this molecule appears to have some toxicity when used at high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these pathways can be an excellent target for cancer therapy. In addition, MAPK and Wnt pathways activated are a marker of poor prognosis in human oral cancer, and persistent MAPK activation in it is associated with enhanced cellular and tumor growth 31 , 32 . The high cytotoxic effect of anethole in oral cancer cells at low concentration but in normal gingival cells, it has a marginal effect at low concentration, but this molecule appears to have some toxicity when used at high concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also demonstrated that proteins such as the receptor for activated C kinase 1 (RACK1), dickkopf-related protein 3 (DKK3) and T-cadherin are crucial for the proliferation and survival of OSCC. These proteins regulate the proliferation and survival of OSCC via the activation of the AKT/mTOR pathway [71,110,111]. Besides, keratin 17 also displayed high expression in OC and this protein promoted tumorigenesis via the stimulation of AKT/mTOR signaling and glucose uptake [67].…”
Section: Proliferation and Survivalmentioning
confidence: 99%
“…This suggested that HF can regulate post-translational modification of PI3K by physically interacting with the protein, as shown by the results of the GO enrichment, KEGG pathway, and molecular docking analyses. It is plausible that HF may directly attenuate the phosphorylation of PI3K at tyrosine 199, as reported in another study (40). The PI3K/ Akt/mTOR pathway is a crucial signaling cascade in living organisms that has to be activated in a variety of cancers and to regulate cell proliferation, invasion, and migration (20,41).…”
Section: Antitumor Effect Of Hf In Mouse Xenograft Model Of Esccmentioning
confidence: 78%